2017
DOI: 10.1016/j.physbeh.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral administrations of insulin-like growth factor-1 suppress food intake in chicks

Abstract: A number of studies have been made on the physiological actions of insulin-like growth factor-1 (IGF-1) in mammals and birds. In mammals, the effects of central administration of IGF-1 on food intake have been examined. For example, intracerebroventricular administration of IGF-1 significantly decreased food intake in diabetic rats, but not in sheep and nondiabetic rats. The chicken is known to be a hyperglycemic animal. Like satiety hormones, plasma IGF-1 levels are elevated postprandially in chickens. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
(56 reference statements)
2
11
0
Order By: Relevance
“…However, McMurtry et al (1996) demonstrated that the half-life of free IGF-1 was 5.17 ± 0.27 min in broiler chickens. We previously confirmed that hepatic IGF-1 mRNA levels were significantly decreased by 6 h of fasting in 8-day-old broiler chicks (Fujita et al, 2017) and by 4 h of fasting in 14-day-old broiler chicks (unpublished data). These findings suggest that the plasma IGF-1 concentration may be significantly decreased under the 6-h fasted condition, which in turn stimulates appetite in broiler chicks.…”
Section: Resultssupporting
confidence: 66%
See 4 more Smart Citations
“…However, McMurtry et al (1996) demonstrated that the half-life of free IGF-1 was 5.17 ± 0.27 min in broiler chickens. We previously confirmed that hepatic IGF-1 mRNA levels were significantly decreased by 6 h of fasting in 8-day-old broiler chicks (Fujita et al, 2017) and by 4 h of fasting in 14-day-old broiler chicks (unpublished data). These findings suggest that the plasma IGF-1 concentration may be significantly decreased under the 6-h fasted condition, which in turn stimulates appetite in broiler chicks.…”
Section: Resultssupporting
confidence: 66%
“…In chickens, the rostral and caudal parts of the brainstem include the DVC and infundibular nucleus (the avian equivalent of mammalian ARC), respectively (Kuenzel and Masson, 1988). In addition, we have reported that the IGF-1 receptor is expressed in these parts of the brain in chicks (Fujita et al, 2017). The plasma IGF-1 concentration was significantly decreased by 48 h of fasting and reversed by 48 h of refeeding in layer chickens (Kita et al, 2002).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations